Політична та державна діяльність Бориса Мартоса в роки Української революції (1917–1921 рр.) - Рекрут, В. (Краєзнавство, 2019)
У статті розглядається політична та державна діяльність Бориса Миколайовича Мартоса
(20.05.1879 – 19.09.1977) в контексті його участі в демократизації українського суспільства та
боротьби за незалежність України після падіння царату. Висвітлюється його участь у становленні
Української Центральної Ради та її Генерального Секретаріату, а також аналізується склад політичних партій УЦР та визначається місце УСДРП в розподілі керівних посад у структурі Ради. Окремо
розглядається внесок Б. Мартоса у запровадження земельної реформи та розробку законодавчої бази
для справедливого розподілу земельних ресурсів України.
Також висвітлюється діяльність Б. Мартоса на посадах діючих урядів Директорії УНР, зокрема на
чолі Ради народних міністрів та міністра фінансів РНМ протягом грудня 1918 – листопада 1919 рр.
Аналізуються заходи Б. Мартоса щодо налагодження діяльності фінансової системи УНР, друкування
українських грошей, матеріально-технічного постачання армії та створення законодавчої бази для продовольчого й товарного забезпечення населення України. Звертається увага на причини відставки Б. Мартоса з посади прем'єр-міністра уряду УНР. The article examines the political and state activities of BorysMykolayovych Martos (20.05.1879 –
19.09.1977) in the context of his participation in the democratization of Ukrainian society and the struggle for
Ukraine’s independence after the fall of the Russian Empire.His participation in the formation of the Central
Council of Ukraine and its General Secretariat is highlighted, and the composition of the political parties of
the Central Council of Ukraine is analyzed, and the place of the Ukrainian Social Democratic Labor Partyin
the distribution of leadership positions within the Council structure is determined.The contribution of B. Martos
to the implementation of land reform and the development of a legislative framework for the equitable distribution
of land resources of Ukraine are considered as well.
The work of B. Martos inthe Government of the Directory of the Ukrainian People’s Republic, in particular
as the head of the Council of People’s Ministers and as Minister of Finance of the Council of People’s Ministers
during December 1918 – November 1919.Actions of B. Martos concerning the establishment of the financial system
of the Ukrainian People’s Republic, the printing of Ukrainian money, the logistical supply of the army and the creation
of a legislative framework for food and commodity provision of the population of Ukraine are analyzed.
Reasons for the resignation of B. Martos from the position of prime minister of the Government of the
Ukrainian People’s Republic are brought to attention.